Defending nature :|a comparative analysis of the Cerattepe and Kirazlı anti-mining environmental movements - Üner, Büşra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
In the last decade, the number of environmental movements that emerged in opposition to the mining projects increased dramatically following the rising pressure of the government, the amendments regarding the mining laws and legislation, and the designation of the new mining areas throughout Turkey. Many of these movements have been organized through similar mobilization strategies like the vigil protests to defend the area; yet, these strategies have substantially changed the ways in which the local actors communicate and ally with each other to sustain the movement. To analyze the organization and mobilization strategies of environmental movements in Turkey, I compare the Cerattepe (Artvin) anti-mining movement with the Kirazlı (Çanakkale) anti-mining environmental movement and question different understandings of environmentalism, its effects on the organization of environmental movements, and the ways in which the local inhabitants are able to forge alliances or not. I argue that when the local actors create a place-based struggle as a part of the organization of an environmental movement it is more likely to sustain grassroots activism through a common ground and diverse alliance like the Cerattepe case. Additionally, the geographical position of the Çanakkale is conducive for the emergence of a new environmentalist group in the province leading to a conflict among different groups of inhabitants. This is why, they could not create a collective identity for a sustainable environmental movement. I name this new environmentalist group as “environmentalism of the urbanite”.
Keywords: Environmentalism.; Environmental justice.; Environmental justice -- Cerattepe.; Environmental justice -- Kirazlı.; Social movements -- Turkey.